Protocatechuic acid prevents reproductive damage caused by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) in male rats - Beytur, A.; Ciftci, O.; Aydin, M.; Cakir, O.; Timurkaan, N.; Yilmaz, F. (Wiley, 2012)
In this study, it was aimed to determinate beneficial effects of protocatechuic acid (PCA) against reproductive toxicity caused by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), an environmental contaminant. For this purpose, 28 rats were equally divided into four groups (control, TCDD 2 mu g kg-1 per week, PCA 100 mg kg-1 per day and TCDD + PCA group), and compounds were orally administered for 45 days. The results indicated that TCDD induced oxidative stress via an increase in thiobarbituric acid-reactive substances levels and a decrease in reduced glutathione, catalase, glutathione peroxidise and SOD levels in male rats. In contrast, PCA treatment prevented toxic effects of TCDD in terms of oxidative stress. Additionally, sperm motility, sperm concentration and serum testosterone levels significantly decreased, and pathologic testicular damage increased with TCDD exposure. However, these effects of TCDD on sperm characteristics, histopathological changes and hormone levels were reversed by PCA treatment. In conclusion, it was found that TCDD exposure induced reproductive toxicity (oxidative, hormonal, histopathological and spermatological alternations) in male rats and PCA treatment could prevent toxic effects of TCDD. Thus, PCA may be useful for the prevention and treatment of reproductive toxicity caused by TCDD.
Keywords: 2; 3; 7; 8-TCDD; protocatechuic acid; reproductive toxicity; testicular damage; testosterone